Formation of ohmic contacts to n(p)-gan and measurement of their contact resistivity - Boltovets, M.S.; Ivanov, V.M.; Konakova, R.V.; Kudryk, Ya.Ya.; Milenin, V.V.; Shynkarenko, V.V.; Sheremet, V.M.; Sveshnikov, Yu.N.; Yavich, B.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
We propose multilayer ohmic contacts to n- and p-GaN layers, with titanium
boride as diffusion barrier. It is shown that the optimal method of contact resistivity
measurement is the transmission line method (TLM) with circular contact geometry. The
Ti−Al−TiBx−Au contact metallization to n-GaN retains its layer structure after thermal
annealing at temperatures up to 900 °C. The contact resistivity ρс is (6.69±1.67)×10⁻⁵
Ω⋅cm². For the Au−TiBx−Ni−p-GaN contact structure, the contact resistivity is
(1±0.15)×10⁻³ Ω⋅cm²
.